2008
DOI: 10.1136/bjo.2008.145912
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month short-term safety and visual-acuity results from a multicentre prospective study of epiretinal strontium-90 brachytherapy with bevacizumab for the treatment of subfoveal choroidal neovascularisation secondary to age-related macular degeneration

Abstract: The safety and efficacy of intraocular, epiretinal brachytherapy delivered concomitantly with anti-VEGF therapy for the treatment of subfoveal CNV secondary to AMD were promising in this small study population. Long-term safety will be assessed for 3 years. This regimen is being evaluated in a large, multicentre, phase III study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 23 publications
1
52
0
2
Order By: Relevance
“…So far, only phase I/II studies for epiretinal brachytherapy in AMD using the VIDION system have been published [13,14]. While the first study demonstrated that a minimum dose of 24 Gy is required to achieve a therapeutic effect [14], the other study demonstrated the effect of brachytherapy combined with two injections of bevacizumab [13].…”
mentioning
confidence: 98%
“…So far, only phase I/II studies for epiretinal brachytherapy in AMD using the VIDION system have been published [13,14]. While the first study demonstrated that a minimum dose of 24 Gy is required to achieve a therapeutic effect [14], the other study demonstrated the effect of brachytherapy combined with two injections of bevacizumab [13].…”
mentioning
confidence: 98%
“…Epimacular brachytherapy is designed to deliver precisely controlled dose of beta radiation to CNV lesion. Compared to previously used radiation therapy strontium-90 beta radiation is ideal for treating retina because its delivery system ensues no collateral damage to surrounding retinal tissues (53,54). After pars plana vitrectomy is done, radiation applicator is placed directly above CNV lesion and held for 2-4 minutes.…”
Section: Epimacular Brachytherapymentioning
confidence: 99%
“…The NVI-111 study 8 of EMB in treatment-naive patients and the MERITAGE study 10 of previously treated patients enrolled only 34 and 53 patients, respectively. Larger trials are needed to validate these early results.…”
Section: Emb Year 1 Year 2 Yearmentioning
confidence: 99%
“…Reports suggest that EMB reduces the number of anti-VEGF injections required to control wAMD, while maintaining or sometimes improving vision. [8][9][10] This report aims to model the cumulative 3-year cost to the NHS of anti-VEGF monotherapy with either ranibizumab or bevacizumab, and then compare this to treatment using adjunctive EMB.…”
Section: Introductionmentioning
confidence: 99%